Exploring Risk Factors and Outcomes of Low-Birth-Weight Infants in the Misurata Medical Center NICU - A Retrospective Analysis (2022) - Elburki, Salima Mukhtar; Assadi, Moktar Ahmed; Agdawra, Faraj Ali; Assadi, Abdulaleem Ahmed; Rajab, Ali Abdulsalam (Journal of medical and pharmaceutical sciences, 2024)
Objective: To examine the characteristics and outcomes of low-birth-weight (LBW) newborns admitted to the NICU at Misurata Teaching Hospital in 2022, and to identify key factors influencing their survival.Patient’s and methods: a retrospective descriptive study included 199 LBW newborns (
Keywords: Low-Birth-Weight Infants; Neonatal Intensive Care Unit; Maternal Factors; Neonatal Factors